Media Effectiveness of Sports Nutrition Quartet Card in Increasing Knowledge Football School Athletes - Maya Triana; Mardiana Mardiana (Universitas Negeri Semarang, 2024)
Background: Knowledge is one of the factors that can affect a person's behavior or diet. Therefore, efforts in communication, information, and education (KIE) regarding sports nutrition are needed to support athletes' eating behavior. This study aims to analyze the effectiveness of the Sports Nutrition Quartet Card media in increasing the knowledge of football school athletes. Methods: This type of research is the ADDIE model's research and development (R&D). The implementation of the developed product uses an Experimental Quasy research design with a Pretest-Posttest Control Group Design. The sample amounted to 44 people, with details of 22 people in the experimental group and 22 in the control group determined by simple random sampling. The data analysis technique uses the t-test followed by the N-Gain test. Results: The study results showed that the assessment of media and material experts was obtained with an average percentage of 79.5% or very feasible. From the field trial results, a percentage score of 81% was obtained or very practical. The t-test results showed a difference in the knowledge of athletes (p<0.05), followed by the N-gain score of 0.44 in the medium category. Conclusion: It can be concluded that the Sports Nutrition Quartet Card medium is quite effective in increasing the knowledge of football school athletes.